EFISIENSI WAKTU DAN BIAYA DALAM PENGGUNAAN ALAT BERAT PADA PEKERJAAN PEMELIHARAAN OVERLAY RUAS TOL CIPULARANG JALUR A - Syapril Janizar; Faisal Hadi Abdullah (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
Toll roads are transportation infrastructure that has a very important role in supporting economic, social, and cultural growth. With the passage of time, toll roads will due to an decrease in conditions such as damage to road pavements, so road maintenance is needed. In toll road maintenance, in the use of heavy equipment is very necessary with the aim of facilitating work in the location. However, if its use is not done wisely, it will experience losses in terms of costs and time, such as not reach the targets or schedules that have been planned, then rental costs and heavy equipment maintenance costs that swell. In order not to experience losses in the use of heavy equipment in a construction project, it is necessary to manage management in the use of heavy equipment by optimizing costs and time so that the use of heavy equipment worth efficiently, and on time as planned.